Telesne značilnosti kegljačev - Pintarič, Primož (Šport (Ljubljana), 2016)
Morphologic characteristics do not correlate with sports results in nine pin bowling. But they can have an impact on athletes health. We tested 107 athletes (60 men and 47 women) with variables of morphologic characteristics. Comparing with normal population they are of similar height, percentage of fat mass and have higher values of muscle mass. We detected asymmetries in arms % in circumferences and mass - between left and righ arm. Also the throwing arm shoulder is lower than oposite one, what can cause vertebra pain or injuries.
Keywords: arms; asimetrije; assimetry; health; kegljanje; morphologic characteristics; nine pin bowling; roke; sport; šport; telesne značilnosti; zdravje